Movimento social, escola e formação: um olhar a partir do IALA Amazônico - Ivanoski, Nicolle Marra (2015)
This work aims to analyze what the formative processes from a very specific reality are the Latin American Institute of Agroecology - Amazonian IALA. For this purpose, some basic premises will be established initially; the first one is related to the importance of comprehending the role of social movement and the strengthening of the Via Campesina international struggle, taking the roots of the Latin-American fight and MST s expressiveness as the main point, detailing the movement s history, its collective actions and the pedagogical elements that compose its formal and non formal educational practices as well. The principle grounds of human formation process and some questions on this matter will be drawn since we defend the centrality of work as an educational principle in this research. Thenceforth, in order to describe and analyze the concept and the organization of the formation processes of the Amazonian IALA, we present some fundamental categories of analyses, such as Self-organization; Omnilateralism; Work and praxis. Through interviews and observations done in field, we attempt to demonstrate the elements that evince these categories as part of the methodological strategies carried in the Amazonian IALA which, differently from the educational practices enrooted in the capitalistic society, consider the collectivity as part of the subject formation and retrieve the educative dimension of work as a theoretical and practical category. Given the main characteristics, challenges and limits of entrenching a counter-hegemonic space of formation aiming to social transformation will be presented too.